Experimental evaluation and numerical modelling of the quality of photovoltaic modules - Kristo Karjust (Estonian Academy Publishers, 2021)
All over the world a rapid increase in demand for photovoltaic system installations has generated an outstanding growth in production numbers in the manufacturing facilities of photovoltaic (PV) systems. Production companies are facing challenges in providing the best quality along with rising manufacturing quantities. Due to the underlying technology not all the quality decisions can be made in real time. This research is focused on the development of experimental study and mathematical modelling of the quality control parameters for PV modules, which could only be tested during chemical processes and not be monitored constantly by operators at the production line.